(untitled) (Journal of Science Foundation, 2017)
Background: The clinical characteristics of hepatocellular carcinoma are varied from person to person. Objectives: The purpose of the present study was to see the clinical profiles of hepatocellular carcinoma patients. Methodology: This cross sectional study was carried out in the Department of Radiology and Imaging in Dhaka Medical College, Dhaka and Banghabandhu Sheikh Mujib Medical University, Dhaka from January 2007 to May 2008 for a period of around one and half year. All the patients presented with hepatocellular carcinoma at the age group of more than 20 years with both sexes were selected as study population. The patients were undergone CT-scan examination and the confirmation was performed by histopathological examination. All the clinical features of HCC patients were recorded. Result: A total number of 50 patients were recruited in this study after fulfilling the inclusion and exclusion criteria. Mean age of my study was 48.78 and SD ± 12.07. Hepatocellular carcinoma commonly presented with hepatomegaly (96%). Upper abdominal pain (60%), weight loss (60%), anorexia (44%), nausea/vomiting (44%), bruit (21%), jaundice (40%) and ascitis (32%) was also present. Conclusion: In conclusion the hepatocellular carcinoma is most commonly occurred in middle age group with a predominance of male. Journal of Science Foundation 2016;14(2):36-39